Fecal Microbiota Transplantation for Clostridioides Difficile Infection in Patients with Chronic Liver Disease - Alireza Meighani; Maryam Alimirah; Mayur Ramesh; Reena Salgia (International Journal of Hepatology)
Background. Fecal microbiota transplantation (FMT) is a well-established therapeutic option for patients with antibiotic resistant Clostridioides difficile infection (CDI). However, the efficacy of FMT in patients with chronic liver disease remains elusive. Aims. We studied the effect of FMT on chronic liver disease (CLD) patients with CDI at our tertiary medical center. Methods. A cohort of all patients who received FMT from December 2012 to May 2014 for refractory or recurrent CDI was identified. Patients were monitored for a year after FMT. Descriptive analysis was conducted to compare the effect of FMT in patients with and without CLD. Results. A total of 201 patients with CDI received FMT, 14 of which had a history of CLD. Nine of these patients exhibited cirrhosis of the liver with a mean Child-Turcotte-Pugh score of 8. CDI development in these patients was associated with recent exposure to antibiotics and was observed to be significantly different between both groups (17% of CLD patients vs. 58% in the general cohort, p=0.01). Four patients with CLD received >1 FMT, of which 2 did not respond to treatment. There was no significant difference between patients with liver disease and the rest of the cohort with regard to FMT response (12/14 (87%) vs. 164/187 (88%), p=0.68). Conclusion. FMT is a safe and effective therapy against CDI for patients with CLD and cirrhosis.